THE INFLUENCES OF THE RENAISSANCE ON UZBEK AND ENGLISH LITERATURE - Halimova Durdona Nurmuhammad qizi; Rahimova Mohlaroyim Mahammadjon qizi (PT. Antis International Publisher, 2024)
This article explores the profound influence of the Renaissance on Uzbek and English literature during the 14th to 17th centuries and the contributions of poets and writers from Uzbek and English during this period, as well as the similarities and differences between Uzbek and English poets and writers during the Renaissance era. The Renaissance had enduring impact on literature, shaping the way writers approached themes, styles, and forms of expression. This influence can still be seen in contemporary literature in various ways.